105k views
6 votes
Use the quadratic formula to solve. Round to the nearest tenth if necessary.
2x^2 -3x -7 = 0

User Dbb
by
5.6k points

1 Answer

12 votes

The quadratic formula is:


(-b + √(b^2 - 4ac) )/(2a) and
(-b - √(b^2 - 4ac) )/(2a)

In this case, a = 2, b = -3, and c = -7

So, we can plug in the numbers to get:


(-(-3) + √((-3)^2 - 4(2)(-7)) )/(2(2)) and
(-(-3) - √((-3)^2 - 4(2)(-7)) )/(2(2))

Simplifying, we get:


(3 + √(65) )/(4) and
(3 - √(65) )/(4)

You need to use a calculator to find what these would be in decimal form. The answer, rounded to the nearest tenth, is: x = 2.8, x = -1.3

User Thastark
by
6.2k points